Clinico-pathological Analysis of Cervical Pap Smear in Patients Attending Gynecology OPD of a Medical College - Tamrakar, Renuka; Ranabhat, Sabin; Shrestha, Madhu; Poudel, Sandesh; Shrestha, Sabita; Khanal, Bandana; Joshi, Rakshya; Sharma, Basant; Khatri, Dhan; Lamichhane, Janak (Europasian Journal of Medical Sciences, 2021)
Background: Cervical cancer ranks the most common cancer among Nepalese women. Cervical and vaginal infections constitute the most common gynecological problems. Through Pap smear screening, early diagnosis, follow up and treatment, morbidity and mortality can be reduced by 70% and 80% respectively. Methods: This retrospective study was conducted to know the incidence of abnormal cervical epithelial lesions and cervico-vaginal infections. It was carried out in the Outpatient Department of Gynecology at Chitwan Medical College from April 2018 to March 2019. The data were collected and standard statistical analysis done using Microsoft Excel 2007. Results: The most prevalent cervical epithelial cell abnormality was atypical squamous cells of undetermined significance (3.43%) whereas the least common was low grade squamous intraepithelial lesion (0.21%). The most prevalent cervical vaginal infection was Bacterial vaginosis (12.30%) whereas the least prevalent was Trichomoniasis (0.29%). The majority of the women with epithelial cell abnormality were in the age group of 31-40 years whereas the lowest number in the age group less than 20 years. The highest prevalence of cervical vaginal infection was in the reproductive age group (31-50 years) and the lowest in the age above 51 years. Most of the patients had multiple symptoms like vaginal discharge, genital itching, whereas only (20.17%) visited for routine screening. Conclusion: Atypical squamous cells of undetermined significance and Bacterial vaginosis were the most common findings in Pap smear test representing abnormal cytology of cervix and cervicovaginal infection respectively.